(untitled) (AACINI - International Journal of Industrial Engineering, 2024)
This work is developed within the framework of an interinstitutional investigation, between the Department of Technology of de National University of Luján and the Faculty of Engineering of the National University of Mar del Plata, with independent professionals linked to the management of human resources, and health professionals who work on the rehabilitation of Persons with Disabilities. This is a preliminary approach, which aims to study the skills required by this group to go through processes of effective labour insertion. For this, a bibliographic survey is carried out, with the purpose of understand the concepts of employability and the associated skills, which allow People with Disabilities to enter and remain in the labor market, adapt, progress and find satisfaction at work. The methodology will be a review of primary and secondary bibliographic sources, from which it is expected to obtain a formal and conceptual basis for the study, to serve as an input to guide future research.